How would I solve this problem in steps? 9/21/2013 | Jen from Brockport, NY | 1 Answer | 0 Votes Mark favorite Subscribe Comment
Hey Jen, is it x - 7 = 1 - 5 5 3x or x - 7 = 1 ? 5 3x-5 I dont want to confuse you w/ the wrong explanation. 9/21/2013 | Justin L. Comment Comments it is the first one? 9/21/2013 | Jen from Brockport, NY x - 7 = 1 - 5 5 3x what you want to do first is make ALL the fractions go away. to do that multiply EVERYTHING by your common denominator. This case it will be 15x. (15x)x - (15x)7 = (15x)1 - 5(15x) -->3x^{2} - 105x = 5 - 75x 5 3x 3x2 - 105x = 5 - 75x <-- make it =0 minus 5 and add 75x to both sides 3x^{2} - 30x -5 =0 quadratic equation to solve for x 30 +- √(30^{2} - 4(3)(-5)) 2(3) 30 +- √(900 + 60) 6 30 +- 30.984/6 30+ 30.984 / 6 and 30-30.984/6 x=10.164 and x =-.164 9/21/2013 | Justin L. Comment
x - 7 = 1 - 5 5 3x what you want to do first is make ALL the fractions go away. to do that multiply EVERYTHING by your common denominator. This case it will be 15x. (15x)x - (15x)7 = (15x)1 - 5(15x) -->3x^{2} - 105x = 5 - 75x 5 3x 3x2 - 105x = 5 - 75x <-- make it =0 minus 5 and add 75x to both sides 3x^{2} - 30x -5 =0 quadratic equation to solve for x 30 +- √(30^{2} - 4(3)(-5)) 2(3) 30 +- √(900 + 60) 6 30 +- 30.984/6 30+ 30.984 / 6 and 30-30.984/6 x=10.164 and x =-.164 9/21/2013 | Justin L.
Comments
5 3x
5 3x